The Effects of Causal Attributions on Decision Makers' Responses to Performance Downturns - Ford, Jeffrey D. (Academy of Management Review, 1985)
Understanding organizations' responses to performance downturns requires understanding decision makers' attributions of causality. Drawing on Weiner's causal attribution model, this paper presents a framework for categorizing causal attributions and relates them to internal and external response strategies. Characteristics of downturns, organizations, and decision makers that influence attributions and the dynamics of attributions are discussed.